Neurophysiological monitoring during neurosurgery: anesthetic considerations based on outcome evidence - Gruenbaum, Benjamin F; Gruenbaum, Shaun E (Current opinion in anaesthesiology, 2019)
This article reviews the recent outcome studies that investigated intraoperative neurophysiological monitoring (IONM) during spine, neurovascular and brain tumor surgery. Several recent studies have focused on identifying which types of neurosurgical procedures might benefit most from IONM use. Despite conflicting literature regarding its efficacy in improving neurological outcomes, many experts have advocated for the use of IONM in neurosurgery. Several themes have emerged from the recent literature: the entire perioperative team must always work together to ensure adequate communication and intervention; systems and checklists, in which each member of the perioperative team has a clearly defined role, can be useful in the event of a sudden intraoperative changes in electrophysiological signals; regardless of the IONM modality used, any sudden change in electrophysiological signal should prompt an immediate and appropriate intervention; a multimodal IONM approach is often, but not always, advantageous over a single IONM approach. For neurosurgical procedures that can be complicated by neural injury, the use of IONM should be considered according to specific patient and surgical factors. Future studies should focus on improving IONM technology and optimizing sensitivity and specificity for detecting any impending neural damage.